Crise, neoliberalismo e os impactos para o serviço social dos correios - Alves, Katia Anastácio da Silva (2023)
This paper proposed to analyze how the impacts of the process of productive restructuring of capital, implemented in Brazil from the 1990s, were imposed on the performance of the Social Service of the Empresa Brasileira de Correios e Telégrafos – Correios. We know that the process started in the 1990s, in Brazil, is not linear in these more than 30 years of the beginning of the economic and political restructuring of the capitalist world, since the crisis of the 70s/80s of the twentieth century. Our object, then, sought to capture and analyze the most current expressions of this economic, social, political, and cultural phenomenon, which began in the central countries of capitalism extended from north to south of the world. From carrying out a documentary research, we collected official and public domain data that recorded the changes that occurred in the Brazilian Post and Telegraph Company (Post Office or ECT) between the years 2009 to 2022, and we concluded that this company implements policies that dialogue with neoliberal ideals.